SIMULASI KREDIT PEMASARAN MOBIL BEKAS BERBASIS WEB MENGGUNAKAN CODEIGNITER FRAMEWORK - Dadi Rosadi; Purnomo , (Jurnal Computech & Bisnis (e-Journal), 2015)
As increasing competition between similar products sales, especially four-wheel vehicles, CK88 Mobilindo which is one of the used car showroom which is located on Jalan Gatot Subroto no. 225 need to create an innovation and improvement in the conduct of marketing strategies to increase consumer interest in purchasing the products offered.Media advertising is a marketing strategy used CK88 Mobilindo showroom in the used car market vehicles offered. To provide better service to consumers and presents a variety of information to consumers is a good strategy to attract consumers.In this study, a media tool to meet one of the marketing strategies in the showroom CK88 Mobilindo. With applications and Simulation Information Systems Used Car Loan Web-Based Marketing is expected to meet the wishes of the showroom to attract consumers. Keywords: information systems, simulation credit, marketing, CodeIgniter framework